Hybrid multiple-input multiple-output scheme combining precoded and non-precoded transmission - Halmi, Mohd Hairi; Alias, Mohamad Yusoff; Chuah, Teong Chee (Institution of Engineering and Technology (IET), 2011)
A hybrid multiple-input multiple-output (MIMO) scheme capable of switching between non-precoded transmission and covariance-based precoded transmission is proposed. Such a hybrid scheme is desired as the covariance-based precoding gain is insignificant when transmission takes place in lowly correlated channels. Such a minor performance gain is not sufficient to justify the high-complexity precoding employed at the transmitter. The proposed scheme does not require a feedback channel or pilot symbols as knowledge of the downlink channel covariance and correlation is made available to the downlink transmitter through direct estimation from the uplink received signal energy. Performance studies carried out in both time division duplex and frequency division duplex systems reveal that the performance of the proposed scheme is on par with that of an existing MIMO precoding scheme with the added advantage of lower complexity and improved system efficiency.